MOLECULAR DIAGNOSIS OF THE MITOCHONDRIAL DIVERSE GROUP, CLADE A, HAPLOTYPE A5 OF THE HEAD LICE Pediculus humanus capitis IN IRAQ WITH THE INVESTIGATION OF ITS PHYLOGENETIC AND SECONDARY STRUCTURE ANALYSIS - Karwan S. N. AL-Marjan; S. M. A. Abdullah; F. H. Kamel (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate molecular diagnosis of the mitochondrial diverse group (haplogroup and haplotype) of the head lice, Pediculus humanus capitis in Iraq, using CYTB gene sequence analysis. For this purpose, louse sampling was performed over a period ranging from 1st April 2021 to the 31th May 2021 among primary school children in the center of Erbil city, Kurdistan region , Iraq. Genomic DNA from isolated sample were achieved followed by amplify a partial sequence of CYTB and sequencing it. All sequences were recorded in International Center for Biotechnology Information (NCBI) under the accession number, OL684637. OL684638 OL684639 OL684640 and OL684641. BLAST results showed that the query sequence was 97.72% similar to Pediculus humanus capitis, Clade A, Haplotype A5. (identity percentage is 97.44%) which is consider as a first molecular investigation for the determination of the type of genetic diverse group in Iraq. Phylogenetic tree was constructed and the results appear that there is a phylogenetic close relationship with African mitochondrial genetic diverse group.